2022
DOI: 10.1002/slct.202201613
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Mediated Stable Vesicles: A Nano Drug Delivery Vehicle for Anti‐cancer Drugs Curcumin and 5‐Fluorourecil

Abstract: Hierarchical self-assembly of new age surfactants, surface-active ionic liquids (SAILs) has attracted increasing interests because of its close resemblance to membrane mimetic structure and its application in drug delivery. Among these self-assembled structures, thermodynamically stable vesicular nanoaggregates are of great importance due to its structure that can carry both, hydrophilic and hydrophobic molecules within its core and bilayers, respectively. Here, we report the ester functionalized SAILs to syne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…This implies that the vesicular aggregates formed by the ester functionalized morpholinium-based system exhibit robust stability even under conditions of substantial dilution. 21,47 We also show that vesicles and nanocomposites have pH stability using DLS-size (hydrodynamic radius) experiments. 63,64 The size of the NaDC/C 12 EMorphBr vesicles is stable in the pH range of 4-8; however, above pH 8, the vesicles may breakdown and precipitate out of solution, increasing the size of the solution (Fig.…”
Section: Stability Of the Nanoaggregates And Nanocompositesmentioning
confidence: 61%
“…This implies that the vesicular aggregates formed by the ester functionalized morpholinium-based system exhibit robust stability even under conditions of substantial dilution. 21,47 We also show that vesicles and nanocomposites have pH stability using DLS-size (hydrodynamic radius) experiments. 63,64 The size of the NaDC/C 12 EMorphBr vesicles is stable in the pH range of 4-8; however, above pH 8, the vesicles may breakdown and precipitate out of solution, increasing the size of the solution (Fig.…”
Section: Stability Of the Nanoaggregates And Nanocompositesmentioning
confidence: 61%
“…As demonstrated in Table 3 [4] for [Ch][Ol]/GA vesicles it is 44.92 Å, [25a] for Cho/[C 12 EMorph][Br] vesicles it is 36.5 Å. [23]…”
Section: Resultsmentioning
confidence: 95%
“…When electrochemical and fluorescence studies were carried out using Np and IND at different pH levels, it was observed that neutral species undergo a partitioning process between the Bmim-AOT LUVs and water pseudophases, while the anionic species do not partition due to the characteristics of the bilayer. In this way, physicochemical properties such as size, surface charge, partition constants, and other characteristics of the bilayer were investigated to use these vesicles as possible candidates for drug-delivery agents in the future. …”
Section: Introductionmentioning
confidence: 99%